Coexisting Endometrioid Type of Endometrial Carcinoma and Transitional Cell Carcinoma of Right Ovary Representing with Acute Abdominal Discomfort: A Case Report - Süleyman Altunsoy; Miğraci Tosun; Handan Çelik; Mehmet Kefeli; Arif Kökçü; Davut Güven; Devran Bıldırcın (Medical Network, 2009)
Coexisting cancers involving both endometrium and ovary in the female genital tract is a well-recognized phenomenon. However, most of them are metastatic lesions arising from one organ and simultaneous primary cancer occurring in both organs is relatively rare. We report a case with dual primary cancer occurring in both ovaries and endometrium with two different histologies. Recently, a 53-year-old woman presented with abdominopelvic discomfort and had symptoms and signs of acute abdomen was found to have Grade III T1C, Nx Mx transitional cell carcinoma of the right ovary and Grade 1, T1a, Nx Mx endometrial carcinoma of endometrioid type. We present this case with a brief review of references.